ANAK ANGKAT DAN PENGATURAN WASIAT WAJIBAH: PANDANGAN KOMPILASI HUKUM ISLAM - Asep Mahbub Junaedi; Adang Djumhur Salikin (JOURNAL OF LAW AND NATION, 2023)
Adoption constitutes a form of familial bond without severing biological ties with the birth parents. Under the Compilation of Islamic Law (KHI), adopted children are entitled to receive up to one-third of the estate as mandatory bequest from their adoptive parents. This research evaluates the regulations concerning mandatory bequest for adopted children within the KHI framework using a normative juridical method, focusing on legislative aspects. The findings indicate that although providing legal certainty, these regulations have not entirely addressed the interests of adopted children, particularly regarding the allocation of shares. Research recommendations include enhancing legal clarity within the KHI concerning the allocation of shares to adopted children and emphasizing the importance of public awareness and governmental dissemination regarding the regulations of mandatory bequest for adopted children within the KHI, aiming to broaden the general understanding of this matter